The Influence Of Learning Environment, Facilities And Parents’ Social Status On The Learning Outcomes Of Fifth-Grade Elementary School Students - Dyah Ayu; Mulyadi Mulyadi; Ira Irviana (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
This study aims to analyze the influence of the learning environment, learning facilities, and parents' social status on the learning outcomes of fifth-grade students at SDI Tangalla, particularly in Indonesian language subjects. The research is driven by the low student achievement, with only about 60% reaching the Minimum Mastery Criteria (KKM). A quantitative approach was employed using surveys and regression analysis. Data were collected through questionnaires, documentation, and observation of a sample of 60 students. The results indicate that all three independent variables—learning environment, learning facilities, and parents’ social status—have a significant simultaneous and partial influence on students’ academic performance. A supportive learning environment, adequate educational facilities, and higher socio-economic status of parents are positively correlated with improved learning outcomes. This study provides valuable insights for developing educational strategies that consider environmental, infrastructural, and socio-economic factors of students.